2020
DOI: 10.1097/pr9.0000000000000820
|View full text |Cite
|
Sign up to set email alerts
|

Sensory bedside testing: a simple stratification approach for sensory phenotyping

Abstract: Introduction: Stratification of patients according to the individual sensory phenotype has been suggested a promising method to identify responders for pain treatment. However, many state-of-the-art sensory testing procedures are expensive or time-consuming. Objectives: Therefore, this study aimed to present a selection of easy-to-use bedside devices. Methods: In total, 73 patients (39 m/34 f) and 20 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 20 publications
1
48
0
4
Order By: Relevance
“…Standardized protocols permit comparison of one individual to normative values and patients with neuropathic conditions using multicenter databases (5,6,14,(19)(20)(21)(22)(23). Patient stratification according to QST profile has been proposed to identify responders in analgesic trials (24). QST has been used in over 1,000 patients with malignancies to investigate large and small fiber neuropathies associated with chemotherapy agents, including bortezomib, vincristine, taxanes, and platinum compounds (25)(26)(27)(28).…”
Section: Quantitative Sensory Testingmentioning
confidence: 99%
“…Standardized protocols permit comparison of one individual to normative values and patients with neuropathic conditions using multicenter databases (5,6,14,(19)(20)(21)(22)(23). Patient stratification according to QST profile has been proposed to identify responders in analgesic trials (24). QST has been used in over 1,000 patients with malignancies to investigate large and small fiber neuropathies associated with chemotherapy agents, including bortezomib, vincristine, taxanes, and platinum compounds (25)(26)(27)(28).…”
Section: Quantitative Sensory Testingmentioning
confidence: 99%
“…Auf diese wurde auch im Rahmen der physiotherapeutischen Praxis hingewiesen [41]. In diesem Zusammenhang sei betont, dass für die somatosensorische Prüfung bereits ein international breit akzeptierter Methodenkanon entwickelt und Referenztabellen erarbeitet wurden, die sowohl Verfahren mit hoher Präzision als auch einfachere Untersuchungstechniken wie die ‚Bedside QST' umfassen [42,43]. Eine Untersuchung muss sich an solchen Standardwerten orientieren, um nicht einfach ein willkürliches Urteil zu sein.…”
Section: Praktische Umsetzungunclassified
“…74 Attempts at simplifying QST batteries for administration in the clinical setting have been reported and have shown that a variety of simple bedside tools (ice cubes, pinprick, cotton swabs) can reliably be used to quantify numerous QST parameters. [75][76][77][78][79] Further research is warranted via large multi-center trials in order to investigate whether bedside QST batteries can predict response to and improve pharmacologically directed therapies.…”
Section: Physiological Factorsmentioning
confidence: 99%